Fair Trade in the Fields of Florida: The Impact of the Penny-Per-Pound on Tomato Pickers - Hyejin Ku (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2014)
Despite the enduring appeal of fair trade activism, little evidence exists on its effectiveness in improving producer welfare. This paper provides evidence on the direct effects of a fair trade premium on its target beneficiaries, using the case of the Penny-Per-Pound, a program that increased the piece-rate wages received by tomato pickers in Florida. It highlights that in output-constraint settings, common in agriculture, a piece-rate compensation scheme can result in externalities among workers. By inadvertently incentivizing the workers to increase their effort whereas the total output is fixed, the program amplified the externality and generated unforeseen risks for worker displacement.
Keywords: J88; M52; O13; 330; consumer activism; price premium; capacity constraint; natural experiment